2020
DOI: 10.1016/j.jvs.2020.04.170
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Thoracic Aorta Diameter Growth Slows by Age 60 Years With Persistent Age-Dependent Centerline Elongation Throughout Life

Abstract: Thirty-four patients were identified with repaired BTAI as previously described. All endografts were oversized by 0.05 (group 2, F 2,30 ¼ 2.58; P > .05). Maximum injury diameter was significantly different in group 1 before and after CT scans (t 20 ¼ 2.09; P < .05) but not in group 2 (t 19 ¼ 0.93; P ¼ .36) explained by one technical error. Preoperative healthy aortic diameters were significantly different from endograft size in group 1 (F 2,45 ¼ 15.74; P < .00001) and became nonsignificant on follow-up (F 2,41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Over time, the diameter of the native aorta gradually increased. This phenomenon was observed by Endicott et al, who found that the aortic diameter increased by 0.1 mm/year in adults from 20 years age to 80 years of age [29]. It appears that post-TEVAR in patients with previously healthy aorta this process is accelerated.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Over time, the diameter of the native aorta gradually increased. This phenomenon was observed by Endicott et al, who found that the aortic diameter increased by 0.1 mm/year in adults from 20 years age to 80 years of age [29]. It appears that post-TEVAR in patients with previously healthy aorta this process is accelerated.…”
Section: Discussionmentioning
confidence: 55%
“…By synthesizing the findings through a meta-analysis of individual studies, we aimed to gather evidence on the extent of aortic diameter changes, both in the short and long term, following TEVAR in the management of BTAI Our metanalysis demonstrated that the proximal neck and distal neck diameter overall, changes by around 2.5mm, comparing pre and post-intervention imaging. This corresponded with a 10% increase in the proximal aortic neck with respect to normal aortic diameter in the same group of age [29]. Even though these studies reported an intended oversized greater than 10%.…”
Section: Discussionmentioning
confidence: 74%